Pupil adjustments to illusory perceptions of the light intensity of object surfaces - Laeng, Bruno; Canoluk, Hüseyin Berke; Nabil, Shoaib (Frontiers in Human Neuroscience, 2025)
Using infrared eye tracking, we show that when gaze is maintained at the center of one of two equiluminant surfaces of a Cornsweet stimulus, designed by Lotto and Purves, that illusorily appear to be lighter or darker than the other, the eye pupils constrict or dilate, respectively. That is, pupil sizes mirror the subjective experience of differential brightness. Previous studies of pupil responses to illusions of light had focused on illusions of unveridical light sources (e.g., patterns resembling the sun), whereas in the present study, we show pupil adjustments to the illusory brightness of object surfaces within images of realistic scenes. In two control experiments, we also showed that when the edge gradients of the Cornsweet stimulus, which do differ in luminance, were either occluded or presented alone in a black field, there were no differences in pupil diameters. We also conclude that adjustments to the perception of surface reflectance are unlikely to represent anticipatory responses to probable risks of temporary visual impairment (i.e., dazzle to sunlight) and, instead, indicate that a gradual process of disambiguation of the visual scene is sufficient to elicit adjustments to the apparent light intensity of an object’s surface.